BRAND AWARENESS,PRICE IN DETERMINING PURCHASING DECISION PRODUCT ASBHOEL - Faritzal, Adam; Rohendra, Tito; Komala Putri, Ratna (International Journal of Psychosocial Rehabilitation, 2020)
The Asbhoel brand is still unknown to the surrounding community and the average price offered by Asbhoel is higher than competitors. So asbhoel needs to plan or take action to increase Brand Awareness to be at the top of product distribution and can improve purchasing decisions. The purpose of this study is to describe Asbhoel Brand Awareness and the high prices offered from asbhoel products and also to obtain analytical results related to the reasons why the Asbhoel Purchase Decision is high even though the Asbhoel brand is unknown and the price offered is expensive. compared to competitors. The research method used is descriptive- verification. Descriptive method is used to obtain the results of the Brand Awareness study, Price in determining the Purchasing Decision of Asbhoel products. While the verification method is used to determine the effect of Brand Awareness, Price in determining the Purchasing Decision of Asbhoel products. The results showed that the relationship of Brand Awareness was less closely related to purchasing decisions. While the price relationship is closely related to the purchase decision of Asbhoel products. The Asbhoel brand can better introduce its product variants by having different characteristics such as color, design and material indetity. Asbhoel should promote via social media advertisements by listing the price of each product variant up to date and making an active and informative website also more active on Facebook so that it can improve Purchasing Decisions.